Preservation of Microstructure in Peach and Mango during High-pressure-shift Freezing - Otero, Laura (2000)
A histological technique was used to evaluate modifications on the microstructure of peach and mango due to classical methods of freezing and those produced by high‐pressure‐shift freezing (HPSF). With the high‐pressure‐shift method, samples are cooled under pressure (200 MPa) to ‐20°C without ice formation, then pressure is released to atmospheric pressure (0.1 MPa). The high level of supercooling (approximately 20°C) leads to uniform and rapid ice nucleation throughout the volume of the specimen. This method maintained the original tissue structure to a great extent. Since problems associated with thermal gradients are minimized, high‐pressure‐shift freezing prevented quality losses due to freeze‐cracking or large ice crystal presence.